(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed to identify the pattern of the Palestinian economy and its reflection on the unemployment rates of university graduates in Palestine. In order to achieve the objectives of the study, the researcher used the descriptive method in his analytical style, using a questionnaire applied to the graduates of the Palestinian universities (Islamic, Azhar, Al Aqsa). The study sample reached (420) graduates , using a random method. The Palestinian graduates estimation of the pattern of the Palestinian economy in support of solving the problem of unemployment of graduates reached a medium and a relative weight (67.80%), while the degree of appreciation of the unemployment rate of Palestinian university graduates from their point of view came to a great extent and a relative weight (69.80%). These results were suggested. The researcher has a number of recommendations, the most important of which are: the development of new disciplines related to the Palestinian labor market in order to balance between professionals and academics to provide the opportunity for all graduates to engage in the Palestinian labor market and work in accordance with the needs of the Palestinian labor market.